(untitled) (Journal of Imam Al-Kadhim College, 2023)
The drug problem has become one of the most social and humanitarian problems facing societies nowadays. It was not in the past to the extent it is witnessing now, as there is hardly a society devoid of this dangerous scourge, which has worsened and become more widespread, and societies have begun to fear its impact on the economy and the safety and security of its individuals. Because it has become a crime in itself, and the accompanying disintegration of society, the destruction of the family entity, and the danger of the scourge increases day after day, and the focus is on conducting many studies and research that contribute to determining the dimensions of the drug problem, and proposing appropriate solutions to help decision-makers prepare a strategy aimed at developing work from This is a dangerous phenomenon that is devastating society, and intensively prepare educational programs to combat this scourge, and identify the role of public relations in reducing the spread of the drug phenomenon. The goal of this research is to identify the role of public relations in reducing the spread of the drug phenomenon, through what public relations does to reach results that benefit decision-makers, especially society in general and university students in particular. This research deals with (the role of public relations in reducing the spread of the drug phenomenon). A field study was conducted from the point of view of the students of Imam al-Kadhim (peace be upon him) University College. The research relied on the descriptive approach, as it used the survey approach, which is one of the most widely used approaches through which data and information can be collected through the methods and methods of descriptive statistics, and transformed into quantitative data that is capable of statistical treatment and an impact study on Imam Al-Kadhim (peace be upon him) University College. The researcher distributed the scale form to a random stratified sample, is of great importance in obtaining samples representing Imam al-Kadhim (peace be upon him) University College in Baghdad. The field study was conducted on the internal student population of (100) students represent the research community, consisting of The research came from a methodological and theoretical framework, in addition to a field study according to a questionnaire specific to the research problem. The research came out with a set of results, conclusions and recommendations.